EFFECT OF INFORMATION SERVICES USING THE MEDIA FILM TO SELF-CONFIDENCE STUDENT OF CLASS VIII SMP NEGERI 8 METRO - MUDAIM, MUDAIM; FARJANTOKY, BELARDO (Universitas Muhammadiyah Metro, 2015)
Abstract: Pessimism and attitudes that consider themselves weak and does not have the ability when facing a problem will make individual impediment in the task of development. Problems confidence that underlies the research are: a) Students are less confident in the ability it has, b) Students feel pessimistic when faced with an issue, c) Student perception subjectively, d) Students still do not do the work independently, and e) negative minded students with a state-owned. The problems of this study are whether there is an influence of information services using the medium of film to the confidence of eighth-grade students of SMP Negeri 8 Metro. The purpose of this study was to determine whether there is an influence of information services using the medium of film to the self-confidence of students in class VIII SMP Negeri 8 Metro. Subject participant is graders VIII-E total 30 students. Data were collected by questionnaire self-confidence and analyzed the data used is the t-test. The results of this study, shown by the difference in change scores of confidence from the pre-test and post-test of 17.1. Testing the hypothesis obtained calculation results thitung6,036> table = 1.699. The conclusion is that the information services implemented using the film medium can be a positive influence on self-esteem, especially students of class VIII. The advice given is to use the medium of film should be done intensively and more creative by BK teachers in giving information service.Keywords: Confidence, Service Information Using Media Film.